101 tips for telecommuters : successfully manage your work, team, technology, and family - Dinnocenzo, Debra A. (Berrett-Koehler, 1999)
Telecommuting can have a tremendously positive impact on an individual's quality of life, productivity, and peace of mind. But all of the advantages are contingent on being a well-informed telecommuter. Author Debra Dinnocenzo offers specific strategies for successful telecommuting that will enhance effectiveness and prosperity, both personal and professional. Easy-to-implement suggestions offer ways to transfer the knowledge and take the steps necessary to change and improve relationships, processes, resources, and systems, at work and at home. Sections address working well alone, with the family, with a team, and with external partners.